THE INFLUENCE OF INTERNAL BANK VARIABLES ON PROFITABILITY WITH THE BI RATE AS A MODERATING VARIABLE - Gunawan, Ferry Anggriawan; Anggraeni, Anggraeni (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
This study examines the effect of internal variables on the profitability of conventional banks in Indonesia, with the Bank Indonesia (BI) Rate as a moderating variable. Profitability is measured using Return on Assets (ROA), while internal factors include credit risk (Non-Performing Loans/NPL), operational inefficiency (BOPO), credit distribution (Loan to Deposit Ratio/LDR and Loan to Asset Ratio/LAR), and bank size (SIZE). The BI Rate is investigated as a potential moderator in the relationship between NPL and ROA. The research employs a quantitative explanatory approach using secondary panel data from seven conventional banks categorized as KBMI 3, listed on the Indonesia Stock Exchange for the period 2019–2023. Data were collected from official sources, including the Financial Services Authority (OJK), Bank Indonesia, and the Indonesian Central Bureau of Statistics (BPS). Multiple regression analysis, both with and without moderation, was conducted to assess the direct effects of internal variables on profitability and the moderating role of BI Rate. The results indicate that credit risk and operational inefficiency negatively affect bank profitability, whereas optimal credit distribution positively impacts ROA. Bank size shows a negative effect on profitability, suggesting that asset expansion without effective cost control and risk management can reduce performance. The BI Rate, however, does not significantly moderate the relationship between NPL and ROA, implying that internal factors, particularly credit risk management and operational efficiency, play a more dominant role in determining profitability for large-scale banks. Overall, this study highlights the importance of robust internal management practices over external monetary policy in maintaining sustainable profitability. The findings provide insights for bank management, investors, and regulators in enhancing financial performance while mitigating credit and operational risks.